GExplore 1.4: An expanded web interface for queries on Caenorhabditis elegans protein and gene function. Issue 4 (1st October 2016) - Hutter, Harald; Suh, Jinkyo
ABSTRACT: Genetic high-throughput experiments often result in hundreds or thousands of genes satisfying certain experimental conditions. Grouping and prioritizing a large number of genes for further analysis can be a time-consuming challenge. In 2009 we developed a web-based user interface, GExplore, to assist with large-scale data-mining related to gene function in Caenorhabditis elegans . The underlying database contained information about Caenorhabditis elegans genes and proteins including domain organization of the proteins, phenotypic descriptions, expression data and Gene Ontology Consortium annotations. These data enable users to quickly obtain an overview of biological and biochemical functions of a large number of genes at once. Since its inception the underlying database has been updated and expanded significantly. Here we describe the current version of GExplore 1.4, documenting the changes since the original release. GExplore 1.4 now contains information about the domain organization of the proteomes of 9 nematode species, can display the location of Caenorhabditis elegans mutations with respect to the domain organization of the proteins, and includes stage-specific RNAseq gene expression data generated by the modENCODE project. The underlying database has been reorganized to facilitate independent updates of the different parts of the database and to allow the addition of novel data sets in the future. The web interface is available underhttp://genome.sfu.ca/gexplore .